PENGARUH PEMASARAN KONTEN DALAM MENINGKATKAN INTERAKSI KONSUMEN PADA UMKM KOTA PANGKALAN BALAI KABUPATEN BANYUASIN - Us, Lasmiana; Syahrizal, Syahrizal; Vitamagistra, Siti Wahyu (LP2M Universitas Bina Bangsa, 2025)
This study aims to evaluate the effect of content marketing on increasing customer engagement in MSMEs (micro, small, and medium enterprises) in Pangkalan Balai City, Banyuasin Regency. To attract and retain customers, a marketing strategy known as content marketing focuses on the production and distribution of relevant and informative content. This study uses a quantitative approach through a survey method. Data was collected through the distribution of questionnaires to 150 SMEs in the City of Pangkalan Balai, Banyuasin Regency. The results of the study show that content marketing has a positive and significant effect on increasing customer interaction with MSMEs in Pangkalan Balai City, Banyuasin Regency. This research makes a theoretical contribution to add literature on consumer interaction and content marketing in MSMEs; The practical implication of this study is that MSMEs in Pangkalan Balai City, Banyuasin Regency can use effective content marketing strategies to improve their interaction with consumers